Promoting regional development bank complementarity : challenges to Asia and lessons from Europe - Ji, Xianbai (2016)
As the international development finance architecture decentralises, a plethora of regional multilateral development banks (MDBs) emerge. The institutional landscape in Asia is transforming with the establishment of the Asian Infrastructure Investment Bank (AIIB). This working paper aims to shed light on the horizontal relationship between the traditional development actor, the Asian Development Bank (ADB) and the nascent AIIB. Based on the collaborative experiences of the European Investment Bank (EIB) and the European Bank for Reconstruction and Development (EBRD), this paper recommends that ADB and the AIIB should form a tri-partite coordination mechanism to promote cooperation and equality, develop complementary portfolios in terms of sectoral exposure and geographical coverage, and co-fund projects to catalyse greater inter-agency cooperation. The resulting synergies will stitch the two institutions into an interdependent and coherent development finance structure in Asia and beyond.